2017
DOI: 10.1177/1369433217695622
|View full text |Cite
|
Sign up to set email alerts
|

Web crippling strength of cold-formed stainless-steel lipped channels with web perforations under end-two-flange loading

Abstract: This paper presents a finite element investigation into the web crippling strength of cold-formed stainless steel lipped channels with circular web perforations under end-two-flange (ETF) loading. The cases of web openings located both centred and offset to the load bearing plates, are considered. In order to take into account the influence of the circular web openings, a parametric study involving 2,190 finite element analyses was performed, covering duplex EN1.4462, austenitic EN1.4404 and ferretic EN1.4003 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…In terms of web holes, Yousefi et al [6][7][8][9][10] recently conducted a series of web crippling tests on ferritic CFSS unlipped channel sections and proposed strength reduction factor equations for the reduced web crippling strength as a result of web holes; however, only ferritic CFSS was considered. For lipped channel sections, Yousefi et al [11] described a numerical study covering ferritic, duplex, and austenitic CFSS; the results of 2,190 FE models were described. It should be noted that the DBN predictions described herein are based on 17,281 FE models and cover a wider range of parameters, thus allowing unified strength reduction factor equations to be proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of web holes, Yousefi et al [6][7][8][9][10] recently conducted a series of web crippling tests on ferritic CFSS unlipped channel sections and proposed strength reduction factor equations for the reduced web crippling strength as a result of web holes; however, only ferritic CFSS was considered. For lipped channel sections, Yousefi et al [11] described a numerical study covering ferritic, duplex, and austenitic CFSS; the results of 2,190 FE models were described. It should be noted that the DBN predictions described herein are based on 17,281 FE models and cover a wider range of parameters, thus allowing unified strength reduction factor equations to be proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Design guidance on web crippling performance has been summarized in ASCE 8-02 [2], AS/NZS 4673:2001 [28] and EC3 [29], which is a supplementary extension of EC3 [30] for carbon steel. However, when the web crippling strength predictions from these design standards were compared with test data available in the literature, it was found that the test-to-predicted ratio can vary from 0.95 to 1.40, indicating that in some cases they can be inaccurate by as much as 40% [6][7][8][9][10][11][31][32][33]. Thus, there is a need for a comprehensive study on web crippling behaviour of CFSS channel sections with web holes.…”
Section: Introductionmentioning
confidence: 99%
“…This was overcome with the advancements in computing and numerical modelling software in the late 1990s and early 2000s making therefore possible to conduct the first parametric studies successfully [27][28][29][30]. Since then, several research studies on cold-formed steel sections subjected to web crippling have been published with the aim to improve and extend the applicability of the empiric equations given in the above mentioned design standards with a focus on channel sections [31][32][33][34][35][36], channel sections with perforations [37][38][39][40] as well as proprietary beams [41] and SupaCee sections [42]. With new emerging alloys available in construction and more advance methods of analysis, web crippling studies also exist on cold-formed high strength steel tubes [43], stainless steel [44][45][46][47][48][49][50] as well as aluminium alloys [51][52][53] among others.…”
Section: Introductionmentioning
confidence: 99%
“…For aluminium sections, Zhou and Young [18] conducted a series of tests and numerical investigation on web crippling square hollow sections, again with unstiffened web holes. Yousefi et al [19][20][21][22] proposed unified strength reduction factor equations for the web crippling strength of cold-formed stainless steel lipped channel-sections with circular web openings.…”
Section: Introductionmentioning
confidence: 99%